Exploring the mechanisms of underground economy: A case study of the informal bicycle market in a southern China city - Tian, Robert Guang; Shu, Xiaohui; Liu, Yu (Edelweiss Applied Science and Technology, 2024)
This paper aims to explore the typical mechanisms of the underground economic phenomenon through anthropological and grounded theoretical methodology through an ethnographic study on the site of an informal bicycle market in a city in South China. It investigates and analyzes the formation path and mechanism of the informal bicycle market. Data was collected through unobtrusive observation and in-depth interviews. It follows a grounded theory data analysis procedure based on multiple data sources, such as participant observations, interviews, prior literature, and news reports. The model illustrates how the informal bicycle market is formatted and the mechanisms to maintain its operations. The findings indicated that the development of the informal market affects the efficiency of social resource allocation and, in many cases, may erode the overall system of the national economy. The analysis of the formation path and mechanism of the underground economy represented by the informal market is of great significance for the sustainable development of the social economy.